New record of the critically endangered striped smooth-hound, mustelus fasciatus (Garman, 1913) (chondrichthyes, triakidae), in the southwest Atlantic - Cuevas, Juan Martín (2018)
We report the southernmost known occurrence in the Atlantic Ocean of the striped smooth-hound, Mustelus fasciatus (Garman, 1913). The shark, a female measuring 106 cm TL, was fished in warm coastal waters, with a salinity of 33,189 PSU, of central Argentina (40°52ʹ13ʺ S, 062°18ʹ42ʺ W). This report increases by 205 km southward the known range of this endemic and Critically Endangered species.